ANALISIS PENILAIAN TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL SELAMA PANDEMI (STUDI KASUS PADA PT. BPD PAPUA PERIODE 2021-2023) - Landjang, Xenia Irene Sandy; Mangopo, Yuni Riskita; Toii, Indra Eka Wardana; Damanik, Lisa Gresti Sella (Gapenas Publisher, 2025)
This research was conducted to evaluate the health condition of banks during the COVID-19 pandemic. The analysis was carried out using the CAMEL approach, using several financial ratios, namely CAR (Capital Adequacy Ratio), KAP (Productive Asset Quality), ROE (Return on Equity), BOPO (Operating Costs to Operating Income), and LDR (Loan to Deposit Ratio). The method used in this study is descriptive with a quantitative approach. The data analyzed is sourced from the Published Financial Statements of PT. BPD Papua during the period 2021 to 2023. The results of the analysis show that during the pandemic, the level of financial health of PT. BPD Papua is generally in the healthy category, supported by high capital strength, good credit and expense management, and stable liquidity conditions.